Treatment of Well Water Using Biosorbent Derived From Areca Fiber Waste - Devie Novallyan; Wiji Utami; Risnita Risnita; Atik Sahara; Malia Sabrina (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
Abstract: The biosorption of well water using biosorbent from areca fiber waste of Jambi province has been performed to elevate well water quality. In environmental preservation, this research aimed to reduce a solid waste of areca fiber waste, which has only been burned so far. This activity would increase carbon emissions in the atmosphere. These materials were obtained using carbonizations (300 and 400 oC) and without carbonization. The proper material is used as a biosorbent was 400 oC sized 200 mesh. The material showed several functional groups on the biosorbent surface, such as hydroxyl, amide, amine, and carbonyl. Interestingly, using this material, the water quality can be increased by treatments of odor, color, pH, TDS, TSS, and E. coli under conditions 1.25 g biosorbent, 50 oC, and 150 rpm for 30 minutes. The adsorption results were compared with the value from the standard of Permenkes No.146/Menkes/Per/IX/1990. Based on the explanation, it is resumed that biosorbent derived from areca fiber waste is effective, inexpensive, and easy to operate for increasing well water quality.Abstrak: Adsorpsi air sumur menggunakan biosorbent dari limbah sabut pinang Provinsi Jambi telah dilakukan untuk meningkatkan kualitas air sumur. Pada pelestarian lingkungan, penelitian ini bertujuan untuk mengurangi limbah padat sabut pinang, yang selama ini hanya dibakar. Kegiatan ini akan meningkatkan emisi karbo ke atmosfir. Material-material ini diperoleh menggunakan karbonisasi (300 dan 400 oC) dan tanpa karbonisasi. Material yang tepat digunakan sebagai biosorben adalah 400 oC berukuran 200 mesh. Material ini memperlihatkan beberapa gugus fungsi pada permukaan biosorben, seperti hidroksil, amida, amina, dan karbonil. Menariknya, penggunaan material ini, kualitas air dapat ditingkatkan menggunakan treament aroma, warna, pH, TDS, TSS, dan E.Coli pada kondisi 1,25 gram biosorben, 50 oC, 150 rpm, dan selama 30 menit. Hasil adsorpsi dibandingkan dengan nilai standar Permenkes No.146/Menkes/Per/IX/1996. Berdasarkan penjelasan, hal ini disimpulkan bahwa biosorben dari limbah sabut pinang efektif, dan mudah untuk menggunakan untuk meningkatkan kualitas air sumur.